I would like to construct infinitely many Pythagorean triples where c = b+3. Proving there are infinitely many should not be difficult but finding the right form for a b and c is proving to be difficult. I have tried modifying the typical a=n^2 + m^2 b=2nm c=n^2-m^2 but that hasn't worked out for me yet. Any suggestions on what to start with? Thanks!

  • $\begingroup$ Do you mean to have $a$ as the hypotenuse? That is, are your triples $b^2+c^2=a^2$ and you want $c=b+3$. Or could it also be $a^2+b^2=c^2$ where $c=b+3$? I ask since the usual choice of letters for Pythagorean triples is to have $c$ be the hypotenuse, but in your attempt of the post it seems you use $a$ for the hypotenuse. $\endgroup$ – coffeemath Dec 17 '13 at 5:44
  • $\begingroup$ Pythagorean triplets have the form $(A(M^2-N^2), 2AMN, A(M^2+N^2)).$ Put $A=3$ and $M-N=1.$ $\endgroup$ – DanielWainfleet May 28 '17 at 22:23

We look first at the simpler problem of Pythagorean triples $(x,y,z)$ where $z=y+1$.

Such a triple must be primitive, and therefore $z=u^2+v^2$, $y=2uv$, for some $u$ and $v$. Then $u^2+v^2=2uv+1$, giving $u=v+1$. That gives the triple $x=2v+1$, $y=2v(v+1)$, $z=2v^2+2v+1$.

Multiply each entry by $3$ to get infinitely many triples $(a,b,c)$ where $c=b+3$.

All triples $(a,b,c)$ with $c=b+3$ must be of this form. For any triple has shape $(k(u^2-v^2), 2kuv, k(u^2+v^2))$ for some $u,v$ that are relatively prime. The possibility $k(u^2+v^2)=k(u^2+v^2)+3$ need not be considered, since $k(u^2+v^2)$ and $k(u^2-v^2)$ always have the same parity.

Putting $k(u^2+v^2)=2kuv+3$, we get $k(u-v)^2=3$, which forces $k=3$.


Another way is to specialize the ascent in the ternary tree of Pythagorean triples (see below). Specializing $\,z = y+3\,$ in the $\rm\color{#c00}{\,formula\,}$below yields the following generation rule

$$ x^2 + y^2 = (y+3)^2\ \Rightarrow\ (6-x)^2 + Y^2 = (Y+3)^2,\quad Y = y-2x+6 $$

This yields $\ (-3,0,3)\to (-9, 12, 15)\to (-15, 36, 39)\to (-21, 72, 75)\to (-27, 120, 123)\,\ldots$ which are simply $\,3\,$ times the triples $\,(a,b,b+1),$ in the highest branch in the tree.


The reflection that yields the descent in the triples tree is the following

$\quad\quad \color{#c00}{(x,y,z)\; \mapsto} (x,y,z) - 2 \dfrac{(x,y,z)\cdot(1,1,1)}{(1,1,1)\cdot(1,1,1)} (1,1,1)$

$\quad\quad\quad\quad\quad\quad = (x,y,z) - 2 \; (x+y-z) \; (1,1,1)$

$\quad\quad\quad\quad\quad\quad = \color{#c00}{(-x-2y+2z, \; -2x-y+2z, \; -2x-2y+3z)}$

We ascend the tree by inverting this reflection, combined with trivial sign-changing reflections:

$\quad\quad (-3,+4,5) \mapsto (-3,+4,5) - 2 \; (-3+4-5) \; (1,1,1) = ( 5,12,13)$

$\quad\quad (-3,-4,5) \mapsto (-3,-4,5) - 2 \; (-3-4-5) \; (1,1,1) = (21,20,29)$

$\quad\quad (+3,-4,5) \mapsto (+3,-4,5) - 2 \; (+3-4-5) \; (1,1,1) = (15,8,17)$

Continuing in this way enables one to reflectively generate the entire tree of primitive Pythagorean triples. This has a beautiful geometric interpretation in terms of reflections - see my said MathOverflow post and see here for sums of four squares.


First, note that we have $a^2=c^2-b^2=6b+9$. We want this to be a perfect square; it's easy to see that we must have $3|b$ and modular considerations show we have to have $2|n$; a little computation suggests to us that $b=6n(n+1)$ is always a perfect square, with $a^2=36n^2+36n+9=9(2n+1)^2$. Now $a^2+b^2=36n^2+36n+9+36n^4+72n^3+36n^2=9(4n^4+8n^3+8n^2+4n+1) = (6n^2+6n+3)^2=(b+3)^2$.

So the requested triple is $(6n+3,6n^2+6n,6n^2+6n+3)$. I doubt there are others, but I'm not going to prove that.

  • $\begingroup$ André Nicolas has proven that these are the only such triples, FYI. $\endgroup$ – user98602 Dec 17 '13 at 5:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.